Distinct Roles for Two Chromosome 1 Loci in Ethanol Withdrawal, Consumption, and Conditioned Place Preference - Kozell, Laura B.; Denmark, Deaunne L.; Walter, Nicole A. R.; Buck, Kari J. (Frontiers in Genetics, 2018)
We previously identified a region on chromosome 1 that harbor quantitative trait loci (QTLs) with large effects on alcohol withdrawal risk using both chronic and acute models in mice. Here, using newly created and existing QTL interval-specific congenic (ISC) models, we report the first evidence that this region harbors two distinct alcohol withdrawal QTLs (Alcw11 and Alcw12), which underlie 13% and 3-6%, respectively, of the genetic variance in alcohol withdrawal severity measured using the handling-induced convulsion. Our results also precisely localize Alcw11 and Alcw12 to discreet chromosome regions (syntenic with human 1q23.1-23.3) that encompass a limited number of genes with validated genotype-dependent transcript expression and/or non-synonymous sequence variation that may underlie QTL phenotypic effects. ISC analyses also implicate Alcw11 and Alcw12 in withdrawal-induced anxiety-like behavior, representing the first evidence for their broader roles in alcohol withdrawal beyond convulsions; but detect no evidence for Alcw12 involvement in ethanol conditioned place preference (CPP) or consumption. Our data point to high-quality candidates for Alcw12, including genes involved in mitochondrial respiration, spatial buffering, and neural plasticity, and to Kcnj9 as a high-quality candidate for Alcw11. Our studies are the first to show, using two null mutant models on different genetic backgrounds, that Kcnj9 -/- mice demonstrate significantly less severe alcohol withdrawal than wildtype littermates using acute and repeated exposure paradigms. We also demonstrate that Kcnj9 -/- voluntarily consume significantly more alcohol (20%, two-bottle choice) than wildtype littermates. Taken together with evidence implicating Kcnj9 in ethanol CPP, our results support a broad role for this locus in ethanol reward and withdrawal phenotypes. In summary, our results demonstrate two distinct chromosome 1 QTLs that significantly affect risk for ethanol withdrawal, and point to their distinct unique roles in alcohol reward phenotypes.